Fear and the internalization of external regulation – An exploratory study on how fear of COVID-19 affected the internalization of mask-wearing - Jonas Tögel; Christof Kuhbandner (PLoS ONE, 2026)
The internalization of externally regulated behavior is a key topic in motivational psychology. While fulfilling the basic psychological needs for autonomy, competence, and relatedness provides the foundation for internalization, less is known about factors that determine its depth. This study examined the role of fear in shaping the internalization of externally regulated behavior, using mask wearing during the COVID-19 pandemic as a real-world example. The continued use of masks after mandate removal provided a natural context to examine how fear influences internalization, as the goal of mask wearing, preventing COVID-19 infection, was potentially associated with strong fear. Following the end of the mandate, participants ( N = 445) were presented with an everyday scenario and asked whether they would wear a mask. Their motivational states across different types of internal regulation, fear of COVID-19, and beliefs about the effectiveness and side effects of mask-wearing were assessed. Analyses showed that higher levels of fear of COVID-19 were strongly associated with continued mask-wearing. Each one-point increase in fear corresponded to a 2.5-fold increase in the odds of voluntarily maintaining mask use. The likelihood of continued mask-wearing increased with stronger beliefs in mask effectiveness and decreased with higher perceived side effects; however, the effect of fear was independent of these rational beliefs and persisted even among individuals who perceived masks as less effective or with stronger side effects. Regarding the depth of internalization, fear of COVID-19 correlated positively with introjected and identified regulation, but not with integrated or intrinsic regulation. These results indicate that fear can facilitate the internalization of externally regulated behavior independently of rational beliefs about the effectiveness and side effects of the behavior, yet only up to a moderate level of self-determination.